Solubility of Drug Olopatadine Mouth Dissolving Film (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: This study was to perform their solubility of drug olopatadine oral film to evaluate their solubilitymouth dissolving film in different solvent and artificial saliva and drug olopatadine hydrochloride solubility indifferent solvent. Materials and Methods: The olopatadine hydrochloride film was prepared by solvent castingmethod that is used for prepared oral strip solubility study in ex vivo method for avoid animal testing this studyeasy to help for solubility testing of film in saliva dissolution time solubility of drug to check in ultravioletspectrophotometricmethod. Results: The prepared oral strip showed satisfactory results for the evaluationparameters oral strip as optimized batch was evaluated. Conclusion: Overall this study indicated the enhancingthe solubility of a poorly water soluble drug and this film formulation is easily solubilized the drug and itsbioavailability is increased. Solubility of drug in different solvent is study in this formulation.